Nazrul’s Humanistic Approach in Promoting Interfaith Harmony: An Analysis of His Literary Works (Social Science Review, 2026)
National poet of Bangladesh, Kazi Nazrul Islam (1899-1976), is profoundly venerated in the chronicles of Bengali literature. Furthermore, he has proved to be more than just a great litterateur. He truly emerges as a unifying force in the realm of interfaith understanding and cooperation. This paper investigates how the humanistic spirit catalyzes the poet’s psyche to solidify the concept of interfaith harmony. In addition, it acknowledges his substantial contributions to the discourse on religious tolerance and the unity of mankind. This paper adopts a qualitative approach in its investigation, textual sources and semi-structured interviews with distinguished academicians with extensive knowledge of the subject matter. The paper concludes that the poet has acquired a profound sense of intercommunal belonging by incorporating humanistic ideals and syncretic beliefs. In a world frequently marked by religious discord, this further suggests that his inclusive philosophy may serve as a guiding force in promoting interfaith harmony and collaboration. Regarding the implications of this research, it has significant value in paving the way for future studies in disciplines such as religion, literature, culture, history, politics, and conflict analysis, among many others.Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 231-244